Identification of SRSF1 binding site regulating BIM splicing and its role in leukemia drug response - Tan, Cheryl Weiqi (2017)
BCL-2-Interacting Mediator of Cell Death (BIM) is a pro-apoptotic BH3-only protein that plays an important role in regulating apoptosis. Hence, its deregulation is often observed in cancer as well as drug resistance. Alternative splicing give rise to different BIM transcripts, which translates into either apoptotic BIM that contains BH3 domain encoded by exon 4, or non-apoptotic BIM that contains exon 3, which is mutually exclusive with exon 4. Trans-acting factor SRSF1, also an oncoprotein, had been shown to activate exon 3 splicing, decreasing apoptotic BIM levels. In this project, we investigate how SRSF1 regulates BIM splicing through overexpression studies. Using exonic splicing enhancers (ESEs) as potential binding sites, BIM minigenes with mutated or deleted ESEs were co-transfected with pCGT7-SRSF1 overexpression plasmid and we noted the changes in the ratio of exon 3 to exon 4 containing transcripts. We observed that ESE3 mutant and deletion minigenes respond the least to SRSF1 overexpression as compared to the other ESEs, suggesting that SRSF1 could be binding at ESE3. We further verified by RNA pull-down, where SRSF1 was bound to wild-type ESE3 but not the mutated ESE3. This identification would benefit the development of diagnostics or therapeutics interventions for deregulated BIM splicing in diseases.